Interactions between leaf phenological type and functional traits drive variation in isoprene emissions in central Amazon forest trees - Robin, Michelle; Römermann, Christine; Niinemets, Ülo; Gershenzon, Jonathan; Huang, Jianbei; Nelson, Bruce W.; Taylor, Tyeen C.; de Souza, Vinícius Fernandes; Pinho, Davieliton; Falcão, Lucas; Lacerda, Caroline; Duvoisin Júnior, Sérgio; et al. (Frontiers in Plant Science, 2024)
The Amazon forest is the largest source of isoprene emissions, and the seasonal pattern of leaf-out phenology in this forest has been indicated as an important driver of seasonal variation in emissions. Still, it is unclear how emissions vary between different leaf phenological types in this forest. To evaluate the influence of leaf phenological type over isoprene emissions, we measured leaf-level isoprene emission capacity and leaf functional traits for 175 trees from 124 species of angiosperms distributed among brevideciduous and evergreen trees in a central Amazon forest. Evergreen isoprene emitters were less likely to store monoterpenes and had tougher and less photosynthetically active leaves with higher carbon-to-nitrogen ratios compared to non-emitters. Isoprene emission rates in brevideciduous trees were higher with a higher diversity of stored sesquiterpenes and total phenolics content. Our results suggest that the way isoprene emissions relate to growth and defense traits in central Amazon trees might be influenced by leaf phenological type, and that isoprene may participate in co-regulating a chemical-mechanical defense trade-off between brevideciduous and evergreen trees. Such knowledge can be used to improve emission estimates based on leaf phenological type since, as a highly-emitted biogenic volatile organic compound (BVOC), isoprene affects atmospheric processes with implications for the Earth’s radiative balance.